Students’ Synthesis Problems in Writing Their Literature Reviews at The English Education Department of Halu Oleo University - Hartina, Rini Darianti; Mursalim, Mursalim; Muhsin, Muhammad Khusnun (Journal of Teaching of English, 2021)
The objectives of this research were to find out: (1) students‘ synthesis problems in writing their literature reviews at the English Education Department of Halu Oleo University; (2) factors that affect students‘ synthesis problems; (3) solutions to overcome those problems. This research used qualitative research design and employed content analysis method, since the undergraduated students‘ theses were qualitatively analyzed to find out their synthesis problems in writing their literature reviews. The researcher used 6 of the undergraduated students‘ theses, which each both of them came from different research areas, such as teaching, linguistic and literature, and the interview result as the data sources. The instruments of this research were a rubric and an interview guideline. In collecting and analyzing the data, the researcher used a rubric that consisted of 1 to 4 range score and 3 measuring criterias, such as source variety, language focus, and organization, to measure students‘ level of synthesis and to know in which criteria did students mostly had problem with in synthesizing literature reviews of their theses, and also interview guideline to explore respondents‘ perspectives on synthesis information. The results of this research revealed that:(1) 5 out of 6 theses got low level of synthesis, whereas, 1 thesis got moderate level of synthesis, and all of those theses got the same problem in source variety criteria; (2) there were several factors that hindered students‘ ability to write a literature review, especially in synthesizing information; (3) therefore, the researcher offered solution related to how to write a good literature review. To conclude, it was clear that synthesis information should gain more attention in order to produce a good literature review in thesis writing.